Complicated pansinusopathy. A case Presentation - Dianarelys Villafuerte Delgado; Bárbara Aleida García Hernández; Alejandro Díaz González; Nery María Díaz Yanes (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2021)
Sinusitis is a frequent entity within the conditions of the paranasal sinuses. It is an inﬂamatory disorder of the nose, and one or more of the paranasal sinuses; its diagnosis is clinical. The complications of sinusitis at the orbital, bone and intracranial levels are an unusual circumstance, but extremely serious; in these, computed tomography plays an important role for diagnosis and evolution; in specific cases, magnetic resonance imaging can be very timely. The case of an adolescent with right eyelid edema, moderate proptosis and signs of disorientation is presented. The result of computed tomography of the skull and orbits reported evidence consistent with complications due to pansinusopathy. The interpretation of the imaging study was essential for the diagnosis and immediate conduct.